Factors Affecting the Audit Quality of Financial Statements of Listed Businesses - Uyen, Tran Tu (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2020)
Financial statements are written records that convey the business operations and financial performance of a company, directly affecting investors' decisions. However, at present, the awareness of investors or auditing firms is still limited in controlling the quality of audits. Through quantitative research methods and multivariate regression analysis to measure the level of influence of these factors, the article has found 5 factors affecting the audit quality of financial statements of listed businesses which include (1) Auditing firm size, (2) In-depth skill of auditors, (3) Quality control procedures at the audit firm, (4) Price of auditing, (5) Service range of the auditing company. Then, the study made a number of recommendations for independent auditing companies and related agencies to improve the audit quality of financial statements of listed companies, at the same time, to find the development direction for the audit profession.